2006
DOI: 10.1128/mcb.00352-06
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-3 Phosphatase Myotubularin-Related Protein 6 Negatively Regulates CD4 T Cells

Abstract: Intracellular Ca2؉ levels rapidly rise following cross-linking of the T-cell receptor (TCR) and function as a critical intracellular second messenger in T-cell activation. It has been relatively under appreciated that K ؉ channels play an important role in Ca 2؉ influx into T lymphocytes by helping to maintain a negative membrane potential which provides an electrochemical gradient to drive Ca 2؉ influx. Here we show that the Ca 2؉ -activated K ؉ channel, KCa3.1, which is critical for Ca 2؉ influx in reactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 30 publications
4
57
0
Order By: Relevance
“…Thus, these findings, together with the demonstration that PI3KC2β enzyme activity is increased in TRIM27 −/− lymphocytes, supports a model whereby direct ubiquitination of PI3KC2β by TRIM27 results in the inhibition of PI3KC2β's enzymatic activity leading to decreased levels of PI3P, resulting in decreased histidine phosphorylation and activation of KCa3.1 by NDPK-B (Fig. S7) (19,40,41,47).…”
Section: Th1supporting
confidence: 51%
See 1 more Smart Citation
“…Thus, these findings, together with the demonstration that PI3KC2β enzyme activity is increased in TRIM27 −/− lymphocytes, supports a model whereby direct ubiquitination of PI3KC2β by TRIM27 results in the inhibition of PI3KC2β's enzymatic activity leading to decreased levels of PI3P, resulting in decreased histidine phosphorylation and activation of KCa3.1 by NDPK-B (Fig. S7) (19,40,41,47).…”
Section: Th1supporting
confidence: 51%
“…Whole-cell patch clamping on activated CD4 T cells (47) and Jurkat-KCa3.1 T cells, PI3P rescue experiment and Ca 2+ imaging were performed as previously described (19) and detailed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…KCa3.1 is expressed at low levels in resting naïve CD4 T cells and is transcriptionally activated following TCR stimulation, leading to increased numbers of KCa3.1 channels in activated cells (10,30,31). We found that KCa3.1 channel activity is also markedly up-regulated following differentiation into Th1 and Th2 cells, and KCa3.1 accounts for the majority of the K + current in these cells.…”
Section: Discussionmentioning
confidence: 63%
“…Whole-cell patch-clamping was performed on activated CD4 T cells 48 h after stimulation with anti-CD3 and anti-CD28 antibodies as described (19) with some modification (30).…”
Section: Methodsmentioning
confidence: 99%
“…MTMR6, a member of the myotubularin family of 3Ј-phosphatases with specificity for PtdIns(3)P and PtdIns(3,5)P 2 ( Fig. 1), binds the K Ca 3.1 calcium-activated potassium channel through coiledcoil domain interaction (49). The K Ca 3.1 channel is essential in the maintenance of the membrane potential that drives Ca 2ϩ influx during activation of naive and memory CD4 ϩ T cells.…”
Section: Evidence For a Role Of Other Lipid Phosphatases In T Lymphocmentioning
confidence: 99%